Comparative Effects of Oven-Drying on Quality of Selected Leafy Spices - Ndife, Joel; Ubbor , Stella; Chinweikpe, Augusta; Onwuzuruike, Anselm (Indonesian Food Science and Technology Journal, 2022)
There has been increasing interest in culinary spices for their health benefits besides flavour. This study assessed the comparative effect of oven-drying on the chemical composition of selected leafy spices. Fresh Uziza (Piper guineense), Curry (Murraya koenigii), Nchanwu (Ocimum gratissimum), Parsley (Petroselinum crispum) and, Mint leaves (Mentha spicata) were assessed for proximate composition, then dried in an oven at 65 Â°C for 25 min. The dried spice leaves were analysed for their proximate composition, mineral contents, phytochemicals, antioxidants, and sensory properties. Proximate analysis showed that moisture content of fresh leafy spices reduced (8.76-10.23%) after drying (3.15 to 5.02%) while fat (1.57-2.83), protein (4.64-5.87%), fibre (1.15-2.83%) and ash (7.89-11.15%) increased after drying. Mineral contents of spices ranged from 7.15-140.05 mg/100g for sodium, 10.04-330.90 mg/100g for potassium and 12.75-305.30 mg/100g for calcium. Parsley spice leaves had the highest concentration of investigated phytochemicals, total polyphenols (43.36 mg/100g) and vitamin C (20.76%). Nchanwu leaves had the highest DPPH activity (75.66%) while Mint leaves had the highest FRAP (Î¼mol/g) and vitamin E (29.98%). The sensory acceptability scores were high (6.95-8.00). The results reveal that oven-drying improved the concentration of nutrients and antioxidant activities and is effective in preserving leafy spices.